Voice Recognition Applied to Real Estate mCRM - João P. ANTÃO; Rúben F. PEREIRA; Ricardo RIBEIRO (Communications of International Proceedings, 2022)
At a time when digital transformation is mandatory for business sustainability and the real estate industry is no exception. The use of mobile customer relationship managers (mCRM) has proven to be an essential tool for brokers in this process, since they work in a highly mobile environment. An mCRM presents itself as advantageous for continuing to involve people's emotions in the business, but with insgihts more conducive to better control of each client's expectations. Yet, despite recognizing the relevance of mCRM many brokers admit not using it leading to the problem of adoption of the tool. Thus, this research proposes the use of voice recognition as one of the features capable of automating and simplifying the introduction of knowledge in an mCRM. Using the methodology of design science research (DSR) this functionality was evaluated, through interviews, with experts in the real estate sector. As main conclusions are perceptible the high user satisfaction and success rate in the use of voice recognition for information introduction in a context of high user mobility.
Keywords: Mobile Customer Relationship Management (mCRM); Voice Recognition; Speech to text; Real Estate.